Estudo químico e avaliação de atividades biológicas da planta Cenchrus echinatus L. (Poaceae) - Silva, Adriano Antonio (2008)
The specie Cenchrus echinatus L., popularly known as "capim-carrapicho", is one of the weeds that hinder the agronomical cultivation of several species, as wheat, cotton, soy, etc., due to its fruit's thoms and for the fact that this species quickly invades, even in bad conditions, several types of soils. There aren't many studies on the isolation and characterization of substances produced by this species, as well as no studies on biological activities of this plant. However, there are several studies that seek the control and/or elimination of this species, with the intention of getting better farming productivity where C. echinatus is a weed. For this, in the present work, it was done the phytochemical study of the species Cenchrus echinatus L., in order to evaluate the biological potential, as well as to isolate biologically active compounds or to enrich the knowledge on substances produced by this plant. There were obtained hexanic, methanolic and acid aqueous extracts of the seeds, as well as methanolic extract of the roots and leaves of C. echinatus. The chromatographic profiles of the extracts were analyzed through TLC and many tests were accomplished, like: oral and topical anti-inflammatory effect, antimicrobial (yeasts and bacteria), antiproliferative, moluscicidal, toxicity against Artemia salina and antioxidant activity. It was also determined the fat acids presence and it was also isolated polyphenolics substances of stilbenoids class. Some of the extracts and partitions presented anti-inflammatory activity, antiproliferative effect, toxicity to A. salina and antioxidant effect. With the analysis of the profile of fat acids in this plant, it was verified the presence of essential fat acids, like omega-3 and omega-6, and others. Three substances were isolated, the pallidol (CE-0l), Carasiphenol C (CE-02) and Nepalensinol B (CE-04).